Comorbidity and Autism Spectrum Disorder Research Topics: Co-Occurrence of Autism Spectrum Disorder and Achondroplasia - Dy, Angel Belle C (Archīum Ateneo, 2019)
This Research Topic in Frontiers aims to overcome the sparsity of studies regarding comorbidity in ASD. It asks potential participants to explore; question; and when necessary; challenge conventional knowledge regarding ASD. Are standard screening instruments capable of delineating the full range of impairment in ASD in the presence of comorbidities? Given the difficulties in communication for many autistic patients; what red flags point towards the presence of comorbidities and what should constitute appropriate medical screening? How do comorbid conditions relate to maladaptive behaviors? This Research Topic will seek answers to these and other questions while raising awareness of how comorbid conditions increase both mortality and morbidity in ASD. Appropriate contributions will include research articles; case reports as well as population-based studies; information for healthcare providers; assessments for clinical management; and position statements from relevant policy making organizations.